The Effect of GCG and Islamic ISR On Company Value with Financial Performance as Moderating Variable in Companies Registered - Ayu Faranisya, Fadiar (Lafadz Jaya Publisher, 2024)
As the sharia economy in Indonesia continues to grow, sharia-based investments, such as sharia stocks, have gained traction. Among these, the Jakarta Islamic Index (JII) stands out as the first sharia stock index, comprising 30 of the most liquid sharia-compliant stocks. The liquidity and performance of companies within JII can be assessed through annual financial reports, which follow sharia principles. This study aims to investigate the influence of Islamic Social Reporting (ISR) and Good Corporate Governance (GCG) on Company Value, with Financial Performance acting as a moderating variable. Specifically, the research focuses on companies listed in JII in 2019, providing insights into how GCG and ISR disclosures impact investor perceptions and firm valuation in the context of sharia-compliant investments. Employing quantitative methods, this research analyzes secondary data obtained from annual financial reports available on the Indonesian Stock Exchange website. The findings will contribute to understanding the role of ISR and GCG in enhancing Company Value and how Financial Performance influences this relationship, offering valuable insights for stakeholders, investors, and policymakers aiming to strengthen the sharia finance sector in Indonesia.